Microbial co-cultivation: discovery of novel secondary metabolites with different biological activities - Pirog, Tatiana; Ivanov, Mykyta (My University, 2023)
In recent decades overuse and misuse of antibiotics as well as social and economic factors have accelerated the spread of antibiotic-resistant bacteria, making them a major problem for humanity. One of the most effective approaches to the discovery of new secondary antimicrobial metabolites is co-cultivation of microorganisms, in which the producer of the target products is grown together with competitive microorganisms (inductors), in response to the presence of which silent biosynthetic genes of the producer strain are activated and an increase in the biological activity of the synthesized secondary metabolites and/or even the synthesis of new metabolites is observed. The review summarizes the current literature data on the co-cultivation of antimicrobial substances producers with competitive microorganisms, which results in the synthesis of new metabolites with antimicrobial and cytotoxic activity, not typical for monocultures. During the co-cultivation of fungi, bacteria, and fungi with bacteria, the synthesis of new antimicrobial and anticancer metabolites, which are classified as alkaloids, phenylpropanoids, macrolides, polyketides, cyclopeptides, terpenoids, anthraquinones, and steroids, is observed. These data indicate that the mixed fermentation of microorganisms is a simple, cheap, and quite effective way to obtain new metabolites that are promising for use in medicine. В останні десятиліття надмірне та неправильне використання антибіотиків, а також соціальні та економічні чинники прискорили поширення стійких до антибіотиків бактерій, зробивши їх основною проблемою для людства. Одним із найефективніших підходів до відкриття нових вторинних антимікробних метаболітів є кокультивування мікроорганізмів, при якому продуцент цільових продуктів вирощують разом із конкурентними мікроорганізмами (індукторами), у відповідь на присутність яких мовчать біосинтетичні гени штам-продуцент активується і спостерігається підвищення біологічної активності синтезованих вторинних метаболітів і/або навіть синтез нових метаболітів. В огляді узагальнено сучасні літературні дані щодо спільного культивування продуцентів антимікробних речовин із конкурентними мікроорганізмами, що призводить до синтезу нових метаболітів з антимікробною та цитотоксичною активністю, нехарактерною для монокультур. При спільному культивуванні грибів, бактерій і грибів з бактеріями спостерігається синтез нових антимікробних і протипухлинних метаболітів, які класифікуються як алкалоїди, фенілпропаноїди, макроліди, полікетиди, циклопептиди, терпеноїди, антрахінони, стероїди. Ці дані свідчать про те, що змішана ферментація мікроорганізмів є простим, дешевим і досить ефективним способом отримання нових метаболітів, перспективних для використання в медицині.
Keywords: кафедра біотехнології і мікробіології; культивування; антимікробні препарати; протипухлинні агенти; co-cultivation; antimicrobial products; anticancer agents